2017
DOI: 10.22616/erdev2017.16.n206
|View full text |Cite
|
Sign up to set email alerts
|

Oil point determination of selected bulk oilseeds under compression loading

Abstract: Abstract. The oil point in oilseeds refers to the minimum pressure, which is required to cause oil to emerge from the oil bearing material. Mechanical parameters relevant to expression of oil from three emerging oilseed crops were determined at their oil points and peak compression under the applied force. Oil contents of the batch of oilseeds used were determined using the soxhlet method. The efficiency of the compressive bulk expression scheme was determined as a function of oil yield determined during mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Although in the present study, to model the behavior of fresh fruit under axial compressive loading, the regression model method has been used, several other methods have been reported to study the behavior of fruit in compressive loading and its modeling. The study of single‐sample (Li, Zhang, & Thomas, 2016), bulk‐sample (Akangbe & Herak, 2017), radial (Ihueze & Mgbemena, 2017), uniaxial (Kabutey et al, 2021), quasi‐static (Hasseldine et al, 2017), and dynamic (Azadbakht, Vahedi Torshizi, & Asghari, 2019) are the prevailing loading methods. Regression or mathematical (Sadrnia et al, 2008), artificial neural network (Vahedi Torshizi, Khojastehpour, Tabarsa, Ghorbanzadeh, & Akbarzadeh, 2020), finite element (Li, Cornish, et al, 2021; Li, Li, & Tchuenbou‐Magaia, 2021), and discrete element (Diels, Wang, Nicolai, Ramon, & Smeets, 2019) are common modeling methods.…”
Section: Resultsmentioning
confidence: 99%
“…Although in the present study, to model the behavior of fresh fruit under axial compressive loading, the regression model method has been used, several other methods have been reported to study the behavior of fruit in compressive loading and its modeling. The study of single‐sample (Li, Zhang, & Thomas, 2016), bulk‐sample (Akangbe & Herak, 2017), radial (Ihueze & Mgbemena, 2017), uniaxial (Kabutey et al, 2021), quasi‐static (Hasseldine et al, 2017), and dynamic (Azadbakht, Vahedi Torshizi, & Asghari, 2019) are the prevailing loading methods. Regression or mathematical (Sadrnia et al, 2008), artificial neural network (Vahedi Torshizi, Khojastehpour, Tabarsa, Ghorbanzadeh, & Akbarzadeh, 2020), finite element (Li, Cornish, et al, 2021; Li, Li, & Tchuenbou‐Magaia, 2021), and discrete element (Diels, Wang, Nicolai, Ramon, & Smeets, 2019) are common modeling methods.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Guy et al (), the bulk density of camelina seeds representing different genotypes was determined in the range of 636–666 kg m −3 . According to Akangbe and Herak () the bulk density of camelina seeds can be up to 1,047 kg m −3 and true density to 1,147 kg m −3 .…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Guy et al (2014), the bulk density of camelina seeds representing different genotypes was determined in the range of 636-666 kg m −3 . According to Akangbe and Herak (2017) with 80 kg N ha −1 to 1.45 g in unfertilized seeds. Czarnik et al (2017) reported an increase in the 1,000 seed weight of camelina when the fertilizer rate was increased from 50 to 100 kg N ha −1 .…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…More oil was given off at the higher compressive stresses than at lower ones. Higher yields, especially during the first compression cycles are explained by the respective pressure ratios (Akangbe & Herak, ). A low pressure ratio results in higher yield while a high ratio limits yield during any compression cycle.…”
Section: Resultsmentioning
confidence: 99%
“…These were observed through lateral orifices located 15 mm from the base of the pressing vessel and with the aid of an auxiliary digital indicator mounted by the pressing rig enabling real-time visual observation of both compressive force and deformation. The pressure ratio (Akangbe & Herak, 2017) is a further treatment of the oil point pressure and refers to the ratio of the pressure at oil point to the applied compressive stress during each compression cycle. where m O (g) is the mass of expressed oil and m ss (g) is the mass of seeds pressed.…”
Section: Determining Mechanical Response and Performance Parametersmentioning
confidence: 99%